Effectiveness of virgin coconut oil (VCO) in increasing immunity in Stunting Toddlers - Iswati, Retno Setyo; Nuraini, Indria (Universitas Wiralodra, 2023)
Stunted toddlers experience chronic malnutrition, which causes a decrease in their immune system, resulting in a higher risk of developing acute and chronic infectious diseases as well as recurrent infections and suffering death. Giving VCO to stunted toddlers aims to improve metabolic function to increase immunity, optimize growth and development, and improve the quality of health status of little toddlers. This research aims to determine the effectiveness of VCO in increasing the immunity of stunted toddlers. This research used a Quasi-Experimental method with 32 stunted toddlers as respondents. The instrument used was a questionnaire given pre-and post-intervention. Data analysis used the Paired t-test. The research results showed that most respondents' immunity level was poor before administering VCO (62.5%). In contrast, after administering VCO, the immunity level of most of the respondents was sufficient (46.9%), with a p-value = 0.01, which means that the administration of VCO has proven effective in increasing immunity in toddlers. It is recommended that the public include VCO as a functional nutrition in therapy for stunting toddlers.